2018
DOI: 10.1186/s12936-018-2434-y
|View full text |Cite
|
Sign up to set email alerts
|

Travel to farms in the lowlands and inadequate malaria information significantly predict malaria in villages around Lake Tana, northwest Ethiopia: a matched case–control study

Abstract: BackgroundIn Ethiopia, malaria has declined in the last decade; only a small number of cases have been reported, primarily from hotspots. The contribution of house proximity to water bodies and the role of migration in malaria transmission has not yet been examined in detail in northwest Ethiopia. Individual and household-level environmental and socio-demographic drivers of malaria heterogeneity were explored contextually in meso-endemic villages around Lake Tana, northwest Ethiopia.MethodsA health facility-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
(78 reference statements)
2
35
0
Order By: Relevance
“…A handful of studies restricted participants to a particular age criteria: both of the Malawi and Ghana studies looked only at children aged < 5 years 20 , 21 , 24 , 25 ; one of the Burkina Faso studies looked only at children aged < 12 years, 13 and one of the Ethiopia studies looked only at adults aged 18 years and older. 14 Some of the studies further specified if travel was to areas that were rural, 12 , 20 22 , 24 , 30 malaria endemic, 16 , 18 , 19 or had an equal/lower or higher transmission intensity, 28 but most of the studies did not.…”
Section: Resultsmentioning
confidence: 99%
“…A handful of studies restricted participants to a particular age criteria: both of the Malawi and Ghana studies looked only at children aged < 5 years 20 , 21 , 24 , 25 ; one of the Burkina Faso studies looked only at children aged < 12 years, 13 and one of the Ethiopia studies looked only at adults aged 18 years and older. 14 Some of the studies further specified if travel was to areas that were rural, 12 , 20 22 , 24 , 30 malaria endemic, 16 , 18 , 19 or had an equal/lower or higher transmission intensity, 28 but most of the studies did not.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the study area, settings, and residential housing are described in detail elsewhere [22]. All the kebeles are within 12 km of Lake Tana, the largest lake in Ethiopia, bordering them in the southwest direction.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that under-five age (36–59 months), travel to malarious lowlands, and inadequate malaria information were independent predictors. Ownership and use of LLINs were low; 69.5% of the participants had no nets [22, 23]. These studies provide information on determinants of malaria prevalence, but they did not explore the behavioral, sociocultural, and socioeconomic contexts explaining why communities did not use LLINs persistently.…”
Section: Introductionmentioning
confidence: 99%
“…Case–control studies are particularly suited to generating evidence of risk factors for rare diseases and have been used for malaria risk factor assessments in settings as varied as Ethiopia, 4 , 5 Namibia, 6 China, 7 and Indonesia. 8 A prior case–control study conducted in Haiti during 2012–2014 found no evidence for a protective effect of consistent insecticide-treated net (ITN) use against symptomatic malaria following a national ITN distribution, but in a context of low rates of consistent ITN use (13% reported using an ITN on all 14 nights in the 2 weeks before the onset of illness).…”
Section: Introductionmentioning
confidence: 99%